2019
DOI: 10.12659/msm.914060
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Enhances the Anti-Liver Cancer Activity of Sorafenib

Abstract: Background Sorafenib, a multiple-target-point kinase inhibitor, has been used as a standard treatment for advanced liver cancer and has shown therapeutic benefits. However, resistance often occurs, prompting the need for identification of synergizing agents. Celastrol is a major active ingredient of Tripterygium wilfordii, which can increase the antitumor effect of traditional antitumor drugs. This work focused on the sensitization of liver cancers in use of celastrol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…To overcome these limitations, one strategy is to combine new agents from natural compounds with standard therapy to reduce adverse effects [ 4 ]. For instance, celastrol, extracted from vine tree roots, enhanced the tumor suppression and apoptosis induction effects of sorafenib [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, one strategy is to combine new agents from natural compounds with standard therapy to reduce adverse effects [ 4 ]. For instance, celastrol, extracted from vine tree roots, enhanced the tumor suppression and apoptosis induction effects of sorafenib [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autocrine VEGF production is one of the key molecular factors to acquire resistance to VEGFR inhibitors in HCC cells [ 30 ]. A recent report has demonstrated that treatment with sorafenib increased VEGF production in human hepatoma cells [ 31 ]. In line with this, our results revealed the autocrine production of VEGF-A in Huh-7 cells under lenvatinib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Celastrol alleviated chronic obstructive pulmonary disease in the lungs of mice ( Shi et al, 2018 ). It has an anti-inflammatory pathway through the suppression of nuclear factor kappa B (NF-κB) signalling ( Zhang et al, 2019 ). In a study conducted on MERS-CoV and SARS-CoV infections, the inflammatory response mediated by NF-κB pathway was regulated by transmembrane serine protease 2 (TMPRSS2) levels within the airway in a TMPRSS2 knockout murine model ( Iwata-Yoshikawa et al, 2019 ; Nabavi et al, 2020 ), suggesting that the inhibition of TMPRSS2 may exert a dual effect on COVID-19, limiting viral entry by reducing the cleavage of the spike protein in ACE2 receptor mediated viral entry ( Hoffmann et al, 2020 ; Nabavi et al, 2020 ).…”
Section: Natural Products As Possible Management/treatment Options Fomentioning
confidence: 99%